2004
DOI: 10.1111/j.1708-8208.2004.tb00213.x
|View full text |Cite
|
Sign up to set email alerts
|

A Three‐Year Follow‐Up Report of a Comparative Study of ITI Dental Implants® and Brånemark System® Implants in the Treatment of the Partially Edentulous Maxilla

Abstract: No statistically significant differences were found between the implants studied, except for the frequency of periimplantitis, which was higher for the ITI implants. The survival rates were high, and the marginal bone loss was small for both systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
104
4
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 17 publications
12
104
4
2
Order By: Relevance
“…According to Albrektsson et al, marginal bone level changes in the first year after implant insertion should be less than 1-1.5 mm and the ongoing annual bone loss should be less than 0.2 mm (24). According to some other authors, the critical values of bone loss following one year after implantation have been proposed to be less than 1.5 mm with the mean 0.1 mm annual rate in the following years (25)(26)(27). In this study, the measured mean mesial and distal bone loss of the implants was less than the mentioned critical value, be considered a success.…”
Section: Discussionmentioning
confidence: 63%
“…According to Albrektsson et al, marginal bone level changes in the first year after implant insertion should be less than 1-1.5 mm and the ongoing annual bone loss should be less than 0.2 mm (24). According to some other authors, the critical values of bone loss following one year after implantation have been proposed to be less than 1.5 mm with the mean 0.1 mm annual rate in the following years (25)(26)(27). In this study, the measured mean mesial and distal bone loss of the implants was less than the mentioned critical value, be considered a success.…”
Section: Discussionmentioning
confidence: 63%
“…According to Albrektsson et al, marginal bone level changes in the first year after implant insertion should be less than 1-1.5 mm and the ongoing annual bone loss should be less than 0.2 mm [11]. According to some other authors, the critical values of bone loss following one year of implantation have been proposed to be less than 1.5 mm with the mean 0.1 mm annual rate in the following years [12][13][14]. In this study, the mean mesial and distal bone loss of the implants were measured less than the mentioned critical value, which may be regarded as successful.…”
Section: Discussionmentioning
confidence: 99%
“…Astrand et al 14 found that rough-surfaced implants had a higher incidence of peri-implantitis than smooth (turned) surfaces, whereas, Wennstrom et al 15 around implants that manifested peri-implantitis and those that were healthy, it was noted that the same types of bacteria were present around diseased and healthy implants; but an increased quantity of bacteria was found at diseased sites. Karoussis et al 24 reported that patients with a history of periodontitis manifested significantly greater probing depths, more peri-implant marginal bone loss, and a higher incidence of peri-implantitis.…”
Section: Jaypee Hs Grover Sagrika Shuklamentioning
confidence: 96%